Mengembangkan Kemampuan Motorik Kasar melalui Kegiatan Pembelajaran Seni Tari pada Anak Kelompok Bermain PAUD Lab School Universitas Nusantara PGRI Kediri - Ayu Titis Rukmana Sari (SELING: Jurnal Program Studi PGRA, 2018)
This study aims to develop gross motor skills through dance learning activities in Playgroup children PAUD Lab. School Universitas Nusantara PGRI Kediri. Gross motor movements involve most parts of the body and usually require power because it is performed by larger muscles, which rely on maturity in coordination. Gross motor abilities of children are expected to develop optimally because directly or indirectly, will affect the daily behavior of children later. Directly, gross motor development will determine the child's skills in moving. Indirectly, the development of gross motor skills will affect the way children see themselves and others. This will be reflected in the general pattern of child adjustment. This research was conducted on 9 Playgroup children in 3 – 4 years old in PAUD Lab. School Universitas Nusantara PGRI Kediri, consisting of 7 boys and 2 girls. This research uses classroom action research method using two cycles. Each cycle consists of four stages, namely planning, action implementation, observation and reflection. Technique of collecting data in this research is observation and documentation. The results of this study indicate that the learning activities of dance art proved able to develop gross motor skills in Playgroup children PAUD Lab. School Universitas Nusantara PGRI Kediri Academic Year 2017-2018.